Niñez, Género y Escritura: La bolsa amarilla de Lygia Boujunga - Lorca, Jorge; Fuenzalida, Valeria (Revista de Teoría del Arte, 2019)
Abstract. The present study, is the product of a two voices interpretive reading, under the wing of a critical and politicized reflection of a seemingly innocuous text, coming from what could prejudicially be thought, a “minor” gender called children’s literature. Our thesis, is that its author, Lygia Bojunga, manages to intelligently stand out from the hegemonic paradigms that dominate the shifting horizon of the own subaltern production conditions that characterize this subgenre, to install an overlapping critical fracture to the normativity of socially stratified roles. In this way, childhood, the feminine, gender roles and writing, emerge as some of the topics chosen and treated here, and that the author manages to disarticulate as the protagonist is suffering and questioning firsthand the naturalization of these same normative social practices that relegate her as a girl and as a woman to spaces encrypted by the power. Without a doubt, the elegance and aesthetic simplicity that the author of “The yellow bag” manages to attach to her work, cohabit in depth with her critical and subversive gaze within that sameinnocent writing that could be thought of as a distracting but falsely inoffensive pyrotechnic effect from the reviled and marginal genre of children’s literature. Its political component operates precisely there, where there seems to be no danger in a lowercaliber, non-academic writing, but that cleverly, in a smuggling mechanism, introduces a critical status of the operations of adultcentrism and prevailing androcentrism.